The Impact of Knowledge Management on Competitive Advantage through the Human Capital at Jordanian Private Hospitals in Irbid (2017-2018) - Hazaimeh, Ali Ahmad Fayez (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to identify the impact of knowledge management on competitive advantage through the human capital at Jordanian private hospitals in Irbid. The researcher used the analytical descriptive approach to deal with the data describing the population; the questionnaire was used to in collecting the data on the variables of study which was analyzed by Statistical Package for Social Science program (SPSS) and (Smart Pls 3) program. The researcher used the comprehensive survey method where consisted of (58) of all managers working in the three administrative levels (Upper, Middle and Lower) in (7) private hospitals in the governorate of Irbid which represent (90.6%) of the study sample. The study found a partial impact of knowledge management with its dimensions (knowledge generation, knowledge distribution and knowledge application) on competitive advantage with its dimensions (providing new services, improving quality and speed of service delivery) through the human capital at Jordanian private hospitals in Irbid. The study recommended attention to dimension of knowledge storage in addition to (knowledge generation, knowledge distribution and knowledge application) at Jordanian private hospitals in Irbid.
Keywords: Knowledge Management; Competitive Advantage; Human Capital; Private hospitals